Analisis cycle time proses perakitan senjata di PT Pindad (Persero) - Fandi Achmadi; Budi Harsanto; Akhmad Yunani (Universitas Mercu Buana, 2021)
This paper aims to analyze the cycle time of the assembly line of one of the weapons products at PT. Pindad (Persero) and to explore the effective methods to improve its performance. The method used is a quantitative analysis of assembly data involving 155 components and 56 tasks distributed over 43 work stations, accompanied by document analysis, especially on scientific literature, to elaborate various appropriate methods to become solutions to the problems encountered. The results show that almost all workstations had a cycle time greater than the takt time. It is also known that there is an imbalance of existing workstations, with the lightest workload lasting 67 seconds while the largest workload lasting 253 seconds. The results of the elaboration of the literature show that several potential methods can provide solutions to the problems encountered by considering the characteristics of the assembly line with a straight-line configuration. This study contributes to the literature by analyzing cycle times and assembly line balances in the defense industry relatively rarely studied in Indonesia.